2019
DOI: 10.1016/j.ijbiomac.2019.02.113
|View full text |Cite
|
Sign up to set email alerts
|

A marine-sourced fucoidan solution inhibits Toll-like-receptor-3-induced cytokine release by human bronchial epithelial cells

Abstract: Fucoidans are sulfated polysaccharides from brown algae, known to have immunomodulatory activity. Their effects on the response of airway epithelial cells to Toll-like receptor 3 (TLR3) stimulation have not been characterized. Our objective was to evaluate the effects of a marine-sourced fucoidan solution (MFS) on the TLR3-induced expression and/or production of cytokines and prostaglandin by human primary bronchial epithelial cells as a model of the airway epithelium. The cells were incubated with MFS in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 52 publications
0
18
0
4
Order By: Relevance
“…3 ) [ 37 ]. Fucoidan is a fucose-enriched and sulfated polysaccharide extracted from brown algae [ 11 , 38 ], which is composed of L-fucose, sulfate groups and small proportions of D-xylose, D-mannose, D-galactose, and D-glucuronic acid in different sources of brown algae ( Fig. 3 ) [ [38] , [39] , [40] ].…”
Section: Application Prospects Of Polysaccharides Against Coronavirusmentioning
confidence: 99%
See 1 more Smart Citation
“…3 ) [ 37 ]. Fucoidan is a fucose-enriched and sulfated polysaccharide extracted from brown algae [ 11 , 38 ], which is composed of L-fucose, sulfate groups and small proportions of D-xylose, D-mannose, D-galactose, and D-glucuronic acid in different sources of brown algae ( Fig. 3 ) [ [38] , [39] , [40] ].…”
Section: Application Prospects Of Polysaccharides Against Coronavirusmentioning
confidence: 99%
“…It is urgent for the international medical community to develop targeted, high-efficiency and low-toxic drugs to treat the coronavirus based on the structure and property of the coronavirus. Polysaccharides have been used in traditional Chinese herbal medicine for at least 500 years [ 11 ], and have advantages of wide sources, low toxicity, good biocompatibility, and immune regulation [ 12 , 13 ]. Some polysaccharides, such as carrageenan, chitosan, fucoidan, and astragalus polysaccharide (APS), have been reported to show strong antiviral activity [ [14] , [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%
“…Fucoidans from Macrocystis pyrifera, A. nodosum , U. pinnatifida , and F. vesiculosus were found to improve immune function by activation of NK cells, DCs, and T cells. Recently, it was considered that fucoidan could inhibit the release of cytokines from human primary bronchial epithelial cells via the Toll-like receptor 3 (TLR3); suggesting that it could relief bronchial inflammation caused by viral infection when applied locally [ 143 ]. Based on results of numerous reports, fucans are promising antiviral agents.…”
Section: Algae-derived Antiviral Compoundsmentioning
confidence: 99%
“…Griffithsin exhibits satisfactory anti-oxidation properties and antitumor activity, which both contribute to its anti-viral efficacy. Fucoidan is a cousin of griffithsin that is widely used to treat liver disease, cancer, and skin infections, due to its anti-inflammatory properties (Dutot et al, 2019 ). During the SARS outbreak, statistical analyses showed that Shandong Province more actively used fucoidan and recorded a significantly lower mortality rate, relative to other regions, possibly due to its “combined strengthening and elimination” abilities.…”
Section: Natural Components and Mechanisms Of Action Against 2019-ncomentioning
confidence: 99%